Investment in Training as a Determinant of Intangible Value: Human Resources Sustainability Model (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
Human capital refers to the set of skills, competencies, knowledge, and experience that generate value within the business framework. This form of capital can also lend a competitive advantage for many companies and is often their most valuable resource. Accordingly, training is one of the critical factors determining an organization's effectiveness. The success of any human resources strategy, incorporating training activities should be measured by what it contributes to the achievement of the organization's stakeholders. Therefore, the analysis and management of these dimensions necessary and important to increase company value. The main objective of this paper is to propose a model that analyzes the influence that accumulated investment in employee training has on the total value of company intangibles. A simple linear regression model is applied to Spanish IBEX 35-listed companies, and results show that a significant investment in human resources is reflected in improved and more sustainable results in the company's future market value.
Keywords: Intellectual Capital; Human capital; Stock market; Stock market value; Investment; Sustainability